2013
DOI: 10.1093/intimm/dxt065
|View full text |Cite
|
Sign up to set email alerts
|

MiR-568 inhibits the activation and function of CD4+ T cells and Treg cells by targeting NFAT5

Abstract: CD4(+) T cells play critical roles in orchestrating adaptive immune responses. Their activation and proliferation are critical steps that occur before they execute their biological functions. Despite the important role of this process, the underlying molecular events are not fully understood. MicroRNAs (miRNAs) have been shown to play important roles in lymphocyte development and function. However, the miRNAs that regulate T-cell differentiation, activation and proliferation are still largely unknown. In our p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 36 publications
4
52
0
Order By: Relevance
“…Moreover, we also showed that miR-568 is overexpressed in CML patients, which has not been previously reported in chronic phase of CML. miR-568 has a role in the activation of CD4 + T cells and, unlike our upward trend in CML, it is downregulated CLL [47,48]. Different expression patterns of miR-568 in CML and CLL could be due to the origin of their lineage in bone marrow.…”
Section: Upregulated Mirnasmentioning
confidence: 61%
“…Moreover, we also showed that miR-568 is overexpressed in CML patients, which has not been previously reported in chronic phase of CML. miR-568 has a role in the activation of CD4 + T cells and, unlike our upward trend in CML, it is downregulated CLL [47,48]. Different expression patterns of miR-568 in CML and CLL could be due to the origin of their lineage in bone marrow.…”
Section: Upregulated Mirnasmentioning
confidence: 61%
“…The transfer of miRs from tumor to immune cells alters their functions, usually downregulating antitumor activities and promoting tumorigenesis (84). Tumor-associated miRs, such as miR-21, miR-155, miR-146a, and miR-568, which have been frequently identified as components of the TEX cargo, regulate the differentiation and functions of various immune cells, often inhibiting effector functions or inducing apoptosis (87)(88)(89)(90)(91). Exosomes in the plasma of patients with different cancer types carry distinct, cancer-specific miR signatures, which appear to correlate with the cancer progression and responses to therapy (92,93).…”
Section: Molecular and Genetic Profiles Of Texmentioning
confidence: 99%
“…NFAT5 also promoted the activation of Tregs by upregulating the expression of IL-2. When NFAT5 was knocked out, the proliferation of Tregs and the production of IL-10 were also inhibited [47]. It is highly like that NFAT5 maintained a balance between different T cell subsets.…”
Section: The Function Of Nfat5mentioning
confidence: 99%